2009
DOI: 10.1021/jp901057w
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of Full-Length Amyloid β 1−42 Tri- and Penta-Oligomers in Solution

Abstract: Amyloid oligomers are considered to play causal roles in the pathogenesis of amyloid-related degenerative diseases including Alzheimer's disease. Using MD simulation techniques, we explored the contributions of the different structural elements of trimeric and pentameric full-length Abeta1-42 aggregates in solution to their stability and conformational dynamics. We found that our models are stable at a temperature of 310 K, and converge toward an interdigitated side-chain packing for intermolecular contacts wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
92
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 87 publications
(198 reference statements)
16
92
1
Order By: Relevance
“…Finally, in a third step, the loop from 27ASN to 30ALA, connecting C-terminal and N-terminal strand, with its hydrophilic residues assumes the form observed in fibrils. The role of C-terminal β-sheet formation as driving force for fibril elongation is also supported by work of Masman et al 29 who studied the same molecule but with different force field. On the other hand, Takeda and Klimov 19 found that the N-terminal strand segment of incoming monomer forms parallel hydrogen bond with the corresponding segments of peptides in the fibril.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Finally, in a third step, the loop from 27ASN to 30ALA, connecting C-terminal and N-terminal strand, with its hydrophilic residues assumes the form observed in fibrils. The role of C-terminal β-sheet formation as driving force for fibril elongation is also supported by work of Masman et al 29 who studied the same molecule but with different force field. On the other hand, Takeda and Klimov 19 found that the N-terminal strand segment of incoming monomer forms parallel hydrogen bond with the corresponding segments of peptides in the fibril.…”
Section: Introductionmentioning
confidence: 64%
“…As experiments have indicated 20,21 that the Aβ peptide deposits to the fibril predominantly as a monomer, we simulate the interaction between a monomer and a pre-structured fibril, and compare our observed monomer structures with the solid-state NMRstructures of Aβ peptides in a fibril. Unlike Buchete et al 28 and Masman et al 29 we study directly the fibril elongation process, not the time-reversed process of aggregate dissociation. By simulating the full-length Aβ 42 peptide we also go beyond previous work that studied similar questions but relied on short fragments such as Aβ (16)(17)(18)(19)(20)(21)(22), 22,23 Aβ(35-40), 24,26 or Aβ(37-42).…”
Section: Introductionmentioning
confidence: 98%
“…19 To obtain an Ab dimer (lowest free energy), two of the same monomers were used. The ClusPro2.0 server, one of the top performers at CAPRI (Critical Assessment of Predicted Interactions) round [13][14][15][16][17][18][19]20 was used to predict the possible structure of the oligomers. We submitted to ClusPro two monomers to obtain the dimer, which was used to dock with another monomer to form a trimer, and so forth; this process was performed until an Ab pentamer was formed.…”
Section: Docking Methodsmentioning
confidence: 99%
“…[41] Vand er Waals forces were treated using a1 .0 nm cutoff. At ime step of 0.002 ps, which had been adopted to successfully deal with such systems, [42,43] was used for our simulations. TIP3P [44] water molecules were filled in adodecahedron box.…”
Section: Computational Models and Methodsmentioning
confidence: 99%
“…Even though in af ibril generated by af ull-length Ab 1-42 ,A b 1-16 is also found to be of disordered structure morphology. [42,49] Thus Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] fragment is difficult to investigate alone. To clarify the inconsistencies and simplifyt he investigation, we adopted an ew center-distance statistical method (CDSM) to analyze the available His coordination sites and their order of priority upon the Cu 2 + binding to mouseo r human Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] .T he reliability of the method is established on ab asis that the metal ion (M) coordination sites of an Ab [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Cdsm Schemementioning
confidence: 99%